German Foreign Policy and its Regional and International Trends at the Beginning of the Twenty-First Century - Salman, Ihsan Abdulhadi (Journal of Legal and Political Studies, 2015)
After the political stability achieved by Germany by rebuilding the political structure after the reunification process, reflected positively on the conduct of its foreign policy. It has benefited from the lessons that her campaign experience of the past and was able to approach the development of its foreign policy, a way that fits with their capabilities and achievements at the level of the new structure and the new external behavior. Germany has found itself the center of the global political developments and take advantage of them. and back success in dealing with these new data to the steps taken in the foreign policy-making process, which depends on the foundations characterized by moderation and consistency and continuity. Also, the key element of German foreign policy which worked by successive governments is reflected in the entry of the country's various forms of joint action and multilateral cooperation in order to achieve its objectives of maintaining international peace and security, and the realization of German foreign policy makers fact the integration of their country with its surroundings is a prerequisite.
Keywords: Germany; Foreign Policy; Regional International Trends; Political stability; Political Structure; Political Developments